Urease Levels and Gastritis Stage in Dyspeptic Patients - Muhammad Miftahussurur; Chyntia Dewi Maharani Putri; Titong Sugihartono; Ari Fahrial Syam; Herry Purbayu; Diah Priyantini; Hartono Kahar; Yudith Annisa Ayu Rezkitha; Iswan Abbas Nusi; Poernomo Boedi Setiawan; Ummi Maimunah; Langgeng Agung Waskito; et al. (Interna Publishing, 2022)
Background: Dyspepsia is a frequent main symptom of inpatients and outpatients scenario in Indonesia. However, the number of endoscopy facilities are still low, thus the use of non-invasive method to detect gastritis is necessary. We measured the relationship between urease levels and the stage of gastritis in dyspeptic adult patients. Methods: A cross-sectional study included outpatient dyspepsia patient from November 2018 to February 2019. We examined 14C-Urea Breath Test (UBT) and determined the stage of gastritis based on the Updated Sydney System classification. Results: The urease level of acute and chronic gastritis positive patients were higher than negative patients (p = 0.001, r = 0.353; p <0.0001, r = 0.433, respectively). The AUC value of 14C-UBT to detect acute, chronic, and atrophic gastritis are 0.889, 0.632 and 0.544, respectively. The best cut-off points of 14C-UBT to predict acute gastritis was ≥26.50δ‰ with sensitivity and specificity being 88.89% and 63.95%, respectively. Whereas the best cut-off points for chronic gastritis was ≥34.50δ‰ with 82.89% sensitivity, 63.16% specificity. As for atrophic gastritis, it showed very low AUC value, hence it is not a sufficient test modality to predict atrophic gastritis cases. Conclusion: 14C-UBT is sufficient for predicting acute or chronic gastritis but not for atrophic gastritis.